Panorama of the presidential reelection in Latin America during the XXI century - Ramos Quistial, Sandra del Carmen (SATHIRI, 2021)
This article discusses the contemporary landscape of presidential re-election in Latin America from the perspective of constitutional engineering and comparative politics, in the context of the re-election trend currently under way in Latin America, which has revived the historical, political and academic debate among those who support and reject presidential re-election. It therefore presents some theoretical and methodological considerations on Latin American presidentialism as a political system and presidential re-election, necessary to understand and study the subject under study, decanting towards the definition of this electoral institution as a decisive factor for the stability and viability of the region’s democracy in the near future. In this way, following comparative logic, the objective of the work is to observe the different modalities of presidential re-election that are being approved in Latin American countries, to visualize what kind of presidential re- lection.can be imposed as a predominant trend. To achieve this goal, we analyze the latest literature onthe influence that re-election can have on Latin American presidentialism as a form of democraticgovernment, and empirically the constant displacement of countries between the modalities ofpresidential re-election so far this 21st century.
Keywords: Presidentialism; Presidential Re-election; Latin America